Genomic DNA Methylation-Derived Algorithm Enables Accurate Detection of Malignant Prostate Tissues - Aref-Eshghi, Erfan; Schenkel, Laila C.; Ainsworth, Peter; Lin, Hanxin; Rodenhiser, David I.; Cutz, Jean-Claude; Sadikovic, Bekim (Frontiers in Oncology, 2018)
NA